COMPARISON OF THE MOTOR AND SENSORY BLOCK BY ROPIVACAINE AND BUPIVACAINE IN COMBINATION WITH LIGNOCAINE IN SUPRACLAVICULAR BLOCK - Soni, Chandni M; Parikh, Hetal (National Journal of Medical Research, 2013)
Introduction: With the introduction of newer and safer local anaesthetics and better advancement in technique for regional anaesthesia, brachial plexus block has taken over. Ropivacaine is a new amino amide local anaesthetic with less cardiotoxicity when compared to Bupivacaine. The aim of our study is to compare ropivacaine 0.75% with bupivacaine 0.5% when both of them are combined with xylocaine 2% in upper limb surgeries under supraclavicular block. Material and Method: In this prospective double blind study, sixty patients of ASA- I and II scheduled for upper limb orthopaedic surgeries were randomly divided into two groups. Group R received Ropivacaine 0.75% 20 ml plus Xylocaine 2% 10 ml while Group B received Bupivacaine 0.5% 20 ml plus Xylocaine 2% 10 ml via supraclavicular route. Results: Group Bupivacaine showed prolonged duration of sensory and motor block and prolonged duration of analgesia compared to Group Ropivacaine but the difference was statistically insignificant. (p>0.05) Conclusion: Ropivacaine 0.75% and bupivacaine 0.5% showed similar onset and duration for sensory and motor block when used for supraclavicular brachial plexus block along with xylocaine. They also provide almost equal duration of analgesia. Because Ropivacaine has a potentially proven safety profile compared to Bupivacaine, it may offer an advantage.